Clinical Significance of Cardiac Murmur in Neonate - Hossain, Mohammad Monir; Akhtar Hasan, Mohammad Nurul; Shirin, Mahfuza; Al Mamun, Mohammad Abdullah; Hossain, Md Delwar (Bangladesh Journal of Child Health, 2012)
Background: There is a popular believe that cardiac murmurs are common in neonate and most are innocent or physiological. However, a cardiac murmur may be the first sign of a serious structural cardiac disease in neonate. Objective: This study was conducted to determine the clinical significance of cardiac murmur as a sole clinical sign in neonate. Methodology: Fifty neonates having cardiac murmur were selected from in-patient department of Dhaka Shishu Hospital from March 06 to October 06. Murmurs were clinically classified as innocent or significant murmur. Echocardiography was done for confirmation of the diagnosis and then patients were reclassified as innocent murmur and structural heart defect. And structural heart defects are further subdivided into physiological variant or significant heart defect. Results: Sixty eight percent cases with murmur were found to have structural heart defect and 32% had innocent murmur. Among the cases with structural heart defect 70.6% were found to have significant heart defect and 29.4% were physiological variant. Clinical suspicion able to differentiate innocent murmur or structural heart defect (p <0.05) as well as physiological variant versus significant heart defect (p <0.05). Conclusion: Confident exclusion of heart disease in the newborn period on clinical examination is probably possible by pediatricians or neonatologists. However, for confirmation of diagnosis, early echocardiographic evaluation is necessary. DOI: http://dx.doi.org/10.3329/bjch.v34i2.10218 BJCH2010; 34(2): 56-61